Blood host preferences and competitive inter-species dynamics within an African malaria vector species complex inferred from signs of animal activity around aquatic larval habitats - Katrina A. Walsh; Deogratius R. Kavishe; Lily M. Duggan; Lucia J. Tarimo; Rogath V. Msoffe; Manase Elisa; Nicodem J. Govella; Markus P. Eichhorn; Emmanuel W. Kaindoa; Fidelma Butler; Gerry F. Killeen (PLoS ONE, 2026)
Background The feeding behaviours of the malaria vector Anopheles arabiensis , and its competitive relationships with other sibling species within the Anopheles gambiae complex, remain largely unexplored within well conserved natural ecosystems, where its known preferred hosts are scarce or absent. Methods Potential aquatic habitats were surveyed for An. gambiae complex larvae across a gradient of natural ecosystem integrity in southern Tanzania, encompassing fully domesticated human settlements, a partially encroached Wildlife Management Area (WMA), and well conserved natural ecosystems within Nyerere National Park (NNP). Direct observations, tracks, spoor and other signs of human, livestock or wild animal activity around these water bodies were recorded as indirect indicators of potential blood source availability. Findings While only An. arabiensis was found in fully domesticated ecosystems, its non-vector sibling species An. quadriannulatus occurred in conserved areas and dominated the most intact natural ecosystems. Proportions of larvae identified as An. arabiensis were positively associated with human and/or cattle activity and negatively associated with distance inside NNP and away from human settlements. Proportions of An. quadriannulatus were positively associated with activities of impala, warthog and possibly bushpig, implicating them as likely preferred blood hosts. While abundant impala and lack of humans or cattle in intact acacia savannah within NNP apparently allowed it to dominate An. arabiensis , presence of warthog seemed to provide it with a foothold in miombo woodlands of the WMA, despite encroachment there by people and livestock. While this antelope and suid are essentially unrelated, both are non-migratory residents of small home ranges with perennial surface water, representing potential hosts for An. quadriannulatus that are widespread across extensive natural ecosystems all year round. Despite dominance of An. quadriannulatus in well-conserved areas, An. arabiensis was even found in absolutely intact natural environments > 40km inside NNP, suggesting it can survive on blood from one or more unidentified wild species. Such self-sustaining refuge populations of An. arabiensis inside conservation areas, supported by wild blood hosts that are fundamentally beyond the reach of insecticidal interventions targeted at humans or livestock, may confound efforts to eliminate this key malaria vector. However, they might also enable insecticide resistance management strategies that could restore the effectiveness of pyrethroids in particular. This new approach to indirectly identifying commonly utilized blood sources may also be applicable to an unprecedented diversity of zoophagic mosquitoes, enabling incrimination of possible bridge vector species capable of mediating pathogen spillover from wildlife reservoirs into livestock and/or human populations.